Enantioselective Construction of Multi-Nitrogen-Containing Spirocycles: Asymmetric [3+2] Annulation of 4-Isothiocyanatopyrazolones with Azodicarboxylates - Wei, Shiqiang; Wang, Wenyao; Xue, Aiqi; Nawaz, Shah; Qu, Jingping; Wang, Baomin (Synthesis, 2021)
The 4-isothiocyanatopyrazolones were exploited as a class of efficient synthons for the construction of triazoline derivatives via asymmetric [3+2] annulation with azodicarboxylates, providing a wide range of structurally diverse multi-nitrogen-containing spirocycles in excellent yields (up to 97%) with excellent enantioselectivities (up to 97% ee).
Keywords: asymmetric catalysis; isothiocyanatopyrazolones; triazolines; annulation; enantioselectivity